Evaluation of the accuracy of shell elements when used for modelling masonry minaret structures under seismic loading - Awla, Halmat Ahmed; Karaton, Muhammet; Taher, Nichirvan Ramadhan; Hamah Sor, Nadhim; Arbili, Mohamed Moafak (Institute for Ionics, 2023)
Solid finite elements are known as the best approach for modelling masonry structures. Since they require large physical memory and are computationally expensive, researchers have consumed efforts to propose simplified alternative methods such as the equivalent frame method, rigid body spring models etc. This study aims to investigate the precision of shell finite elements when employed for modelling masonry minaret structures under seismic loading as another simplified modelling method. For this purpose, the Choly minaret (Mudhafaria minaret) in Erbil city was selected as the case study. The minaret was modelled using solid and shell finite elements. Both models were dynamically analyzed using the El Centro ground acceleration record. Their results in terms of top displacements, maximum stresses, and the frequency of the first seven natural mode shapes were compared. The analysis was up to the elastic limits of the materials used, and inelasticity is not the case in the present work. According to the outcomes of the study, good agreement was seen between the models, and the results indicate that shell finite elements are appropriate for modelling this typology of structures. © 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Masonry minaret structures; Seismic assessment; Shell elements; Solid elements